Pachyphytum confusum (Crassulaceae), a new species from the southwest of the state of Guanajuato, Mexico - Pérez-Calix, Emmanuel; Guadián-Marín, Jesús Israel; García-Ruiz, Ignacio (Instituto de Ecología, A.C., 2018)
Background and Aims: Pachyphytum (Crassulaceae) is a genus endemic to central Mexico, consisting of hanging and succulent plants that grow on cliffs and slopes. The taxonomic information of Pachyphytum is included in general works on Crassulaceae and a series of articles describing new species. At a regional level, it is included in the treatment of the family Crassulaceae for the Flora del Bajío y de regiones adyacentes. The aim of this work is to name and describe a new species of Pachyphytum based on plants collected in the southeast of the state of Guanajuato.Methods: Excursions were realized to one of the localities in the Sierra de Pénjamo from where the plant was registered, as well as to the type locality of Pachyphytum machucae. Descriptions of the collected plants and a comparative table were prepared, and the literature was searched for morphologically similar species. Key results: Pachyphytum confusum is proposed as a species new to science and is compared with P. machucae and P. glutinicaule which it resembles morphologically. The conservation status of Vulnerable (VU) is assigned.Conclusions: Despite the fact that Pachyphytum consists of 21 especies, it is difficult to interprete their relationships; in its last revision two sections were considered; Pachyphytum and Diotostemon; the new species belongs to the first one. The specimens collected in the Sierra de Pénjamo were previously confused with P. machucae, but their comparison showed significant differences in order to consider them as a distinct species. Pachyphytum glutinicaule, another species which it resembles, has a corolla longer than the calyx; however, both species show differences in its petals, bracts and leaves. The inconsistency of the infrageneric classification is discussed in several publications, which is emphasized by the discovery of Pachyphytum confusum.